Response Of Giving Black Jintan Extracts (Nigella Sativa Linn) Of C-Reactive Protein (CRP) In Wistar Rats That Induced Hepatitic Vaccines - Putri Rahayu (NHM PRESS, 1970)
Hepatitis B is a liver inflammatory disease caused by hepatitis B virus. Hepatitis B virus that enters the body will attack the liver cells and do self replication that causes inflammation in the liver. Black cumin has benefits as an immunomodulator with the main content of Thymoquinone that can boost immunity. Thymoquinone may increase macrophage activity through Toll-like receptor (TLR) to microbial phagocytosis so as not to inflammate the cells. Determination of CRP levels is the easiest marker of inflammation. The purpose of this study to evaluate the response of the extract of black cumin (Nigella sativa Linn) on levels of C-Reactive Protein (CRP) in Wistar rats induced hepatitis B vaccine. Black cumin extract as imunomodulator dose 75 mg per kilogram of body weight and 150 mg per kilogram of body weight for 7 days to respond to the levels of CRP in Wistar rats induced hepatitis B vaccine.